Incorrect Use of Face Masks during the Current COVID-19 Pandemic among the General Public in Japan - Machida, Masaki (Int J Environ Res Public Health, 2020)
Since the emergence of the COVID-19 pandemic, the use of face masks by healthy individuals for prevention has been attracting public attention. However, efficacy depends on proper usage. We set out to determine the prevalence of wearing masks to prevent COVID-19 and compliance with appropriate measures for the correct use of face masks among the general public in Japan where wearing medical masks is a “cultural” normality. This cross-sectional study was based on an internet-based survey completed by 2141 people (50.8% men, aged 20–79 years) who were selected among registrants of an Internet research company between 1 April and 6 April 2020. Participants were asked to indicate how often they wore masks for prevention and to what extent they practiced appropriate measures suggested by the World Health Organization. The prevalence of wearing masks was 80.9% and compliance rates with appropriate measures ranged from 38.3% to 83.5%. Only 23.1% complied with all recommendations. Compliance rates were overall low in men and persons with low household incomes. Our results, hence show that many citizens implement inaccurate measures when using face masks. Therefore, providing guidance on correct usage is essential when encouraging the use of face masks to prevent COVID-19.